Analisa Item Response Theory Wonderlic Personnel Test (WPT) - Medianta Tarigan; Fadillah Fadillah (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
AbstractWonderlic Personnel Test (WPT) is a psychology tool that measures individual cognitive abilities based on measuring the level of learning ability, understanding the instruction, and solving the problems. In this study, WPT items were tested using the Item Response Theory (IRT) method. There were 374 participating subjects and the results of the study showed 31 items are fit with the model, while 19 items were misfit. According to the IRT 2PL model analysis, mean of examinee ability was -0.01 (SD=1.19). The mean of difficulty (b) was 0.48 (SD=2.58) and meand of discriminant (a) was 0.62 (SD=0.38). WPT test is indicated to consist of items were misfit, that do not measure the same dimension. These statistical results are in line with the characteristics of WPT which are built from three abilities to measure intelligence.AbstrakWonderlic Personnel Test (WPT) merupakan alat ukur psikologi yang mengukur kemampuan koginitif berdasarkan pada pengukuran tingkat kemampuan belajar, memahami instruksi, dan memecahkan masalah. Dalam penelitian ini dilakukan uji terhadap aitem WPT dengan metode Item Response Theory (IRT). Terdapat 374 subjek yang berpartisipasi dan hasil penelitian menunjukkan 31 aitem sesuai dengan model, sedangkan 19 aitem lagi tidak sesuai. Menurut analisis IRT model 2PL, rata-rata kemampuan peserta adalah -0.01 (SD=1.19). Sedangkan untuk rata-rata tingkat kesukaran (b) sebesar 0.48 (SD=2.58) dan rata-rata daya beda (a) sebesar 0.62 (SD=0.38). Tes WPT diindikasikan terdiri dari aitem yang tidak mengukur satu dimensi yang sama. Hasil statistik ini sejalan dengan karakteristik WPT yang dibangun dari tiga kemampuan untuk mengukur tingkat kecerdasan.